Mucor circinelloides whole-cells as a biocatalyst for the production 3 of ethyl esters based on babassu oil - Andrade, Grazielle S. S. (2014)
The intracellular lipase production by Mucor circinelloides URM 4182 was investigated through a step-by-step strategy to attain immobilized whole-cells with high lipase activity. Physicochemical parameters, such as carbon and nitrogen sources, inoculum size and aeration, were studied to determine the optimum conditions for both lipase production and immobilization in polyurethane support. Olive oil and soybean peptone were found to be the best carbon and nitrogen sources, respectively, to enhance the intracellular lipase activity. Low inoculum level and poor aeration rate also provided suitable conditions to attain high lipase activity (64.8 +/- A 0.8 U g(-1)). The transesterification activity of the immobilized whole- cells was assayed and optimal reaction conditions for the ethanolysis of babassu oil were determined by experimental design. Statistical analysis showed that M. circinelloides whole-cells were able to produce ethyl esters at all tested conditions, with the highest yield attained (98.1 %) at 35 A degrees C using an 1:6 oil-to-ethanol molar ratio. The biocatalyst operational stability was also assayed in a continuous packed bed reactor (PBR) charged with glutaraldehyde (GA) and Aliquat-treated cells revealing half-life of 43.0 +/- A 0.5 and 20.0 +/- A 0.8 days, respectively. These results indicate the potential of immobilized M. circinelloides URM 4182 whole-cells as a low-cost alternative to conventional biocatalysts in the production of ethyl esters from babassu oil. (AU)